2021
DOI: 10.1097/qai.0000000000002733
|View full text |Cite
|
Sign up to set email alerts
|

How Can We Support the Use of Oral PrEP Among Young Women who Sell Sex? A PrEP Cascade Analysis

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…A direct offer of on-site initiation of PrEP to AYP testing HIVnegative might have resulted in increased use. In Zimbabwe, a study with young women who sell sex found that PrEP use was associated with an active offer of PrEP [47]. In Kenya, programmatic data from 89 sites that offered PrEP found that few AGYW were screened for PrEP eligibility and this meant that they were not offered PrEP [48].…”
Section: Discussionmentioning
confidence: 99%
“…A direct offer of on-site initiation of PrEP to AYP testing HIVnegative might have resulted in increased use. In Zimbabwe, a study with young women who sell sex found that PrEP use was associated with an active offer of PrEP [47]. In Kenya, programmatic data from 89 sites that offered PrEP found that few AGYW were screened for PrEP eligibility and this meant that they were not offered PrEP [48].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in table 2, 11 included studies published between 2020 and 2022 (with the newly published relevant conference proceedings) described 6 implementation studies including HPTN 082 Study,27 36 Power cohort study,37 38 Determined Resilient, Empowered, AIDS-free, Mentored and Safe (DREAMS) study in Zimbabwe,39 40 DREAMS study in South Africa,41 MPYA trial42 43 and 3Ps for Prevention study 44 45. The HPTN 082 and Power Cohort studies focused on how to increase PrEP uptake and continuation among high-risk AGYW.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in the two DREAMS projects in South Africa41 and Zimbabwe,39 40 different strategies to increase PrEP uptake and continuation by young women who sell sex (comprising young female sex workers that sell sex and those that do but do not identify as such) were implemented in the context of other HIV prevention strategies. PrEP delivery through peer outreach approach was employed by the DREAMS project in South Africa while PrEP uptake and adherence was promoted through community empowerment and adherence support in Zimbabwe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Descovy has not been approved for use by cisgender women although clinical trials in women are underway. Uptake and persistence with daily pill-taking by women have been low due to a range of barriers [ 4 , 5 , 6 ]. Adherence to product use plays a critical role in maintaining drug exposure required for prevention effectiveness [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%